Design, synthesis and biological evaluation of aryl isoxazole incorporated pyrimidin-2-yl)oxazolo[4,5-b]pyridine derivatives as anticancer agents - Khasim Saheb Shaik; N. Saritha; G. Nagendra Reddy (Results in Chemistry, 2024)
A new library of Aryl Isoxazole Incorporated Pyrimidin-2-yl)oxazolo[4,5-b]pyridine compounds 11a-j and their structures were characterized by analytical data. Further, the preliminary anticancer activity of the newly prepared compounds 11a-j was examined against four types of human cancer cell lines, breast cancer (MCF-7), lung cancer (A549), colon cancer (Colo-205) and ovarian cancer (A2780) by utilizing the MTT method. Most of the compounds displayed good to moderate activities as compared with the etoposide used as a positive control. Amon, five compounds 11a, 11b, 11h, 11i and 11j exhibited more potent activity than the positive control. Mainly, compound 11h displayed superior anticancer activity.